Peningkatan Kapasitas Bisnis pada Kelompok Peternak Ayam KUB Bumdes Cisadane. - Farizah Dhaifina Amran; Tsalis Kurniawan Husain (LPPM Universitas Flores, 2022)
Most of the residents of Salenrang Village have a livelihood as farmers, and there are also those who are engaged in trading or breeding buffalo, cows, horses, goats, chickens, and ducks. Of the several livestock groups in the area, there is the KUB BUMDES Chicken Farmer Group (KPP). KUB chicken (Kampung Unggul Balitnak) is a type of free-range chicken with a new strain produced by the Agricultural Research and Development Agency of Indonesia. The main obstacle to empowering small businesses comes from the entrepreneurs themselves, for example the absence of a bookkeeping system. The market opportunity is quite promising, but continuity and consistency cannot be fulfilled. Limited information and marketing methods make this business not well developed. This activity aims to: (1) Increase entrepreneurship awareness in partner groups, (2) Instill knowledge about business fundamentals in partner groups, (3) Conduct financial management and administration training. This activity is carried out on July-August 2019 by direct guidance, coaching and training methods to partners through three stages, namely: stage 1. Inculcating entrepreneurship awareness, stage 2. Instilling knowledge about business fundamentals, stage 3. Financial management training. The results of this activity found that (1) Awareness of partner group entrepreneurship has grown, (2) understanding of partner group business fundamentals is good, (3) partner group financial management knowledge already exists.